BRAIN NATRIURETIC PEPTIDE AS A PREDICTOR OF CLINICAL OUTCOME AND SYMPTOM IMPROVEMENT AFTER LEFT VENTRICULAR ASSISTANCE DEVICE IMPLANTATION - Terzić, Duško; Nestorović, Emilija; Karan, Radmila; Đurošev, Ivana; Milićević, Vladimir; Karadžić-Kočica, Milica; Marković, Dejan (Medical Research, 2024)
Introduction Predictive value of brain natriuretic peptide in heart failure in known, but its importance as an outcome predictor after LVAD implantation remains unaddressed. This research aims to examine the significance of BNP as an indicator of treatment outcomes during different post-implantation periods. Methods A retrospective cohort study included the analysis of medical records of 87 patients in whom LVAD was implanted at the University Clinical Center of Serbia from 2014 to 2020. The correlation was evaluated of BNP levels with treatment outcomes after operation. Results The average preoperative BNP for all patients was 1244 pg/mL. The average EF was 15% (median), ESD was 6.80 cm and EDD 7.70 cm. 81 patients were NYHA class 4, and 6 patients were NYHA3. Compared by the preoperative BNP level below or above 1000 pg/mL, there was no significant difference in overall survival of patients after operation (Log Rank [Mantel-Cox] test, p=0.838). BNP levels postoperatively decreased from 358 pg/mL at 3 months from surgery to 136 pg/mL 5 years from surgery (Friedman test, p<0.001). BNP levels show strong negative correlation with EF (decrease in BNP level and increase in EF value), and strongly positive correlation with EDD, ESD, and NYHA class (decrease in BNP and decrease in EDD, ESD, and NYHA). Conclusion Preoperative BNP level may not be an adequate predictor of the outcome after LVAD implantation, but the post-implantation decrease in BNP levels is highly correlated with parameters that indicate an improvement in the clinical status and positive changes in the myocardium and long-term survival. Keywords: LVAD, BNP, heart failure, reverse remodeling, NYHA